The Benefits of Nori Fruit Extract (Morinda Citrifolia Linn) in Increasing the Storage of Spermatozoa Y Bali Cows Resulting from Sexing at a Temperature of 5oC - Sri Firmiaty; Muhammad Idrus; Bestfy Anitasari; Hamsina Hamsina (Jurnal Penelitian Pendidikan IPA, 2023)
The sperm sexing technique is the separation of spermatozoa carrying the X chromosome and the Y chromosome, which allows farmers to choose male births for beef cattle businesses. However, the process of centrifugation and sperm preservation can cause oxidative stress which gives rise to free radicals. Therefore, an antioxidant ingredient is needed in the diluent, including noni fruit extract which contains lots of flavonoids. This research aims to analyze the addition of noni fruit extract in a diluent to improve the quality of Y-chromosome spermatozoa at a storage temperature of 5oC. The results of the study showed the results of analysis of the progressive motility of Y-chromosome spermatozoa, showing a decrease in progressive motility, on D7 and D-9 there was a difference between control vs P1 and P2 (P<.05) respectively 37.63% vs 49.96% vs 48.56%, while on day 11 showed a very real difference between P0 vs P1 vs P2 respectively 24.32% vs 36.77% vs 40.87%. The addition of 3% and 5% noni extract can improve the quality of Y spermatozoa stored at 5oC. This is because noni extract contains amino acids, ascorbic acid, and flavonoids as antioxidants so that it is able to prevent free radicals, scavengers, and damage to the spermatozoa plasma membrane can be prevented. The addition of 5% noni fruit extract in the diluent to improve the quality of Y-chromosome spermatozoa at a storage temperature of 5oC for up to 11 days.